Comparative efficacy of Chinese herbal injections for treating acute cerebral infarction: a network meta-analysis of randomized controlled trials - Shi Liu; Jia-Rui Wu; Dan Zhang; Kai-Huan Wang; Bing Zhang; Xiao-Meng Zhang; Di Tan; Xiao-Jiao Duan; Ying-Ying Cui; Xin-Kui Liu (BMC, 2018)
Abstract Background Chinese herbal injections (CHIs) are prepared by extracting and purifying effective substances from herbs (or decoction pieces) using modern scientific techniques and methods. CHIs combined with aspirin + anticoagulants + dehydrant + neuroprotectant (AADN) are believed to be effective for the treatment of acute cerebral infarction (ACI). However, no randomized controlled trial (RCT) has been performed to directly compare the efficacies of different regimens of CHIs. Therefore, we performed a systematic review and network meta-analysis (NMA) to compare the efficacies of different regimens of CHIs for ACI. Methods We conducted an overall and systematic retrieval from literature databases of RCTs focused on the use of CHIs to treat ACI up to June 2016. We used the Cochrane Handbook version 5.1.0 and CONSORT statement to assess the risk of bias. The data were analyzed using STATA 13.0 and WinBUGS 1.4.3 software. Results Overall, 64 studies with 6225 participants involving 15 CHIs were included in the NMA. In terms of the markedly effective rate, Danhong (DH) + AADN had the highest likelihood of being the best treatment. In terms of the improvement of neurological impairment, Shuxuening (SXN) + AADN had the highest likelihood of being the best treatment. Considering two outcomes, injections of SXN, Yinxingdamo (YXDM), DH, Shuxuetong (SXT), HongHuaHuangSeSu (HHHSS), DengZhanXiXin (DZXX) and Shenxiong glucose (SX) plus AADN were the optimum treatment regimens for ACI, especially SXN + AADN and YXDM + AADN. Conclusions Based on the NMA, SXN, YXDM, DH, SXT, HHHSS, DZXX and SX plus AADN showed the highest probability of being the best treatment regimens. Due to the limitations of the present study, our findings should be verified by well-designed RCTs.